The advent of plastic and the gratuitous displacement of traditional food packaging in Singapore (1950s – 1990s) - Benedict, Claudia Marianne (Nanyang Technological University, 2020)
This thesis provides a historical assessment on the shift from using traditional methods of food packaging to plastic packaging in Singapore from the 1950s - 1990s. Currently, single-use plastic food packaging is found everywhere in various eating establishments and is a pressing issue because it makes up for a large amount of Singapore’s overall plastic waste. Although some factors can be attributed to the rise of plastic packaging in Singapore, such as the nation’s water insecurity during the 1970s - 1980s and plastic packaging being deemed as more hygienic than traditional packaging, this paper illustrates that this transition was governed by political-economic factors. By incorporating ideas related to Ecological Marxism and drawing original inferences from various archival sources from the 1950s - 1990s, this paper argues that the transition from using traditional food packaging to plastic packaging was facilitated by the government’s prioritisation of economic growth over the environment, which followed a Western-centric model of development. This paper will illustrate how traditional food packaging methods were deliberately phased out, to make way for ‘modern’ plastic. This thesis reframes the concepts of ‘development’ and ‘modernity’ by contextualising it to the history of food packaging, and thus contributing to Singapore’s environmental history.